SHIFTING OLD TEACHING BEHAVIOR FOR NEW CURRICULUM - Sugianto, Sugianto (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
Begin with â€œthe annual habitâ€ of Indonesian government in which the curriculum will be changed as the change of educational paradigm. This paper then aimed to explain about the urgency of new policy in teaching-learning realm and how the teacher adapt and apply that new curriculum in real teaching-learning situation in the classroom. As matter of fact, based on many surveys conducted by some institutions proved that many teachers in every corner of Indonesia still enjoy teaching in their old teaching behavior. No matter how many times the curriculum changed, the problem is that the teachers find it difficult to adapt with the new curriculum. The difficulty in understanding the resent curriculum may caused by many factors, such as lack of information and teachersâ€™ education. Therefore, this paper explains how the teachers should change their old teaching behavior to support the aim of Indonesian government in empowering and increasing the quality of human resource.